PELATIHAN PEMASANGAN JARINGAN INSTALASI LISTRIK 3 PHASA UNTUK PENGOPERASIAN MOTOR INDUKSI 3 PHASA BAGI SISWA-SISWI SMK NEGERI 2 KARANGANYAR - maju binoto; Fariyono (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
There are two types of alternating current electrical installation networks: single-phase and three-phase. Three-phase electrical networks are used to operate three-phase induction motors. To operate a three-phase induction motor, a proper three-phase electrical installation is required. The installation and connection of three-phase electrical installations must comply with PUIL regulations to prevent short circuits. This was the first time the training participants at SMK Negeri 2 Karanganyar received training on properly installing and connecting three-phase electrical installations. The students had never previously received lessons on installing and connecting three-phase installations. Therefore, the Community Service Team of the D3 Electrical Engineering Study Program at STT